Chiral higher spin gravity in (A)dS4 and secrets of Chern–Simons matter theories - Sharapov, Alexey A. (Nuclear physics B)
Chiral Higher Spin Gravity with cosmological constant is constructed as a Free Differential Algebra, i.e. at the level of equations of motion, which is a smooth deformation of its flat space cousin [34]. Chiral Higher Spin Gravity is a unique class of local higher spin theories; its very existence implies that there is a closed and, most likely, integrable sub-sector of Chern–Simons Matter Theories, which has important consequences both for the theories themselves and for three-dimensional bosonization duality.